2009
DOI: 10.1038/sj.bjc.6605100
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical efficacy of the bioreductive alkylating agent RH1 against paediatric tumours

Abstract: BACKGROUND: Despite substantial improvements in childhood cancer survival, drug resistance remains problematic for several paediatric tumour types. The urgent need to access novel agents to treat drug-resistant disease should be expedited by pre-clinical evaluation of paediatric tumour models during the early stages of drug development in adult cancer patients. METHODS/RESULTS: The novel cytotoxic RH1 (2,5-diaziridinyl-3-[hydroxymethyl]-6-methyl-1,4-benzoquinone) is activated by the obligate two-electron reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Reduction of RH1 activates aziridine residues, which subsequently induce DNA damage (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduction of RH1 activates aziridine residues, which subsequently induce DNA damage (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1.…”
Section: Discussionmentioning
confidence: 99%
“…Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1. This enzymedirected cancer-targeting agent is currently being tested in clinical trials (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). However, the molecular mechanisms underlying the therapeutic effects of the agent on solid tumours have not yet been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies involved the new representative of aziridinyl-benzoquinones, RH1 (2,5-diaziridinyl-3-(hydroxymethyl)-6-methyl-1,4-benzoquinone; Fig. 1), which recently underwent preclinical and Phase-I clinical trials (Ward et al, 2005;Hussein et al, 2009;Danson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%